The effects of teaching practice course on professional development of student teachers - (:unkn) unknown (ELSEVIER SCIENCE BV, 2012)
The purpose of this study is to determine student teachers' views about teaching practice courses and their professional gains from this process. In this qualitative research, participants of the study consisted of student teachers from three teacher training programs at Marmara University and Ataturk Faculty of Education. Data were gathered through three open-ended questionnaires and analyzed in conformity with content analysis to attain patterns related to students' problems and professional gains in this process. According to the results of this study, student teachers have some problems with the faculty members (supervisors) who instruct teaching practice courses and practice teachers in practice schools. Student teachers pointed out some of their expectations from faculty members and practice teachers for the solution of these problems and finally this study revealed that teaching practice courses support student teachers' professional development especially about gaining teaching experience.
Keywords: Teacher training programs; teaching practice course